Dietary lutein supplementation improves immunity and antioxidant status of captive Indian leopards (Panthera fusca). Issue 4 (11th January 2022) - Durge, Sharad M.; Das, Asit; Saha, Subodh K.; Pande, Amit; Thakuria, Dimpal; Saxena, Ankur; Bhardvaj, Yogesh; Verma, Ashok K.
Abstract: Indian leopards kept in zoos are fed solely on carabeef on bone (CBB) diets. Carabeef contains lesser or no carotenoids. Hence, the captive Indian leopard diets are suspected to be deficient in carotenoids while their wild counterparts acquire these pigments from their natural prey. Lutein is a vital carotenoid that plays its role as an antioxidant and immunomodulator. This experiment investigates the effect of lutein supplementation on antioxidant status, immunity, and stress in captive Panthera fusca fed CBB diets. Nine leopards were used based on 3 × 3 replicated Latin square designs in the experiment. Groups CON, LUT20, and LUT40 were supplemented with 0, 20, and 40 ppm of lutein, respectively. Each experiment comprised of 10 days of wash‐out period, 11 days of adaptation, and 4 days of collection. Digestibility of crude protein (CP) was higher ( p < .01) in groups LUT20 and LUT40. Serum concentration of protein, globulin, urea ( p < .05), total carotenoids, total antioxidant capacity (TAC), catalase (CAT) activity, and lymphocyte transformation test (LTT) index were higher ( p < .001) in groups LUT20 and LUT40. Activity of superoxide dismutase (SOD) and serum concentration of immunoglobulin were higher ( p < .001) in group LUT20. Serum concentration of malonaldehyde (MDA) and fecal concentration of cortisol decreased ( p < .001) in groups LUT20 and LUT40. Serum concentration of total immunoglobulin (µg/ml) and LTT were higher in group LUT20. Fecal concentration of cortisol (ng/g) was lower in LUT20 and LUT40. The study concludes that supplementation of lutein at 20 ppm would improve antioxidant status and immunity and alleviate stress in captive Indian leopards.